CONCEPTION OF ACEH GOVERNMENT POLICY IN STRUCTURING THE CONTROL AND USE OF AGRICULTURAL LAND TO REALIZE THE IMPROVEMENT OF FARMERS' LIVING STANDARDS IN ACEH - Ria Fitri; Nursiti; Dedy Yuliansyah; Muammar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This paper aims to examine the policy concept of the Aceh Government and Regency/City Governments in Aceh in structuring the control and use of agricultural land to realize an increase in the livelihood of farmers in Aceh. This research uses qualitative methods, secondary data in the form of field and library data, analyzing relevant documents, government reports, case studies and literature. Article 171 and Article 213 paragraph (2) The Aceh Government has the authority to regulate the use and use of agricultural land autonomously in accordance with the geographic conditions and characteristics of the Acehnese people. The conception of the principle of land must be able to prosper the people, especially the peasants as the basis of Law 56 of 1960 and Government Regulation No. 224 of 1961 can be used as a conception in the formulation of regional policies in Aceh in order to realize a prosperous peasant community. The results show that in Aceh there are many farmers who have land below 0.5 ha and farmers who do not have land and absentee farmers. The reason is that the Aceh Government has not used this authority and has not had the right conception to regulate the control and use of agricultural land to improve the living standards of farmers, while still paying attention to and maintaining the habits that live and develop in the Acehnese people which are sourced from Islamic religious law and customary law.